Association of MTH1 expression with the tumor malignant potential and poor prognosis in patients with resected lung cancer. (July 2017) - Fujishita, Takatoshi; Okamoto, Tatsuro; Akamine, Takaki; Takamori, Shinkichi; Takada, Kazuki; Katsura, Masakazu; Toyokawa, Goji; Shoji, Fumihiro; Shimokawa, Mototsugu; Oda, Yoshinao; Nakabeppu, Yusaku; Maehara, Yoshihiko
Highlights: MTH1 protein expression was associated with malignant tumor traits and smoking habits. MTH1 expression was significantly associated with poor prognosis in NSCLC patients. This study suggests MTH1 may be a novel therapeutic target for NSCLC. Abstract: Objectives: The oxidized purine nucleoside triphosphatase, mutT homolog 1 (MTH1), physiologically sanitizes 8-oxo-dGTP in the nucleotide pool. Previous studies indicated that MTH1 is associated with tumor proliferation and invasion in non-small cell lung cancer (NSCLC) cell lines; however, the role of MTH1 in patients with NSCLC remains unclear. Materials and Methods: Two patient cohorts that underwent surgery for NSCLC in our institution were investigated retrospectively. In one cohort consisting of 197 patients, the associations between MTH1 expression and clinicopathological factors or prognosis were analyzed. In another cohort consisting of 41 patients, the relationship between MTH1 expression in the tumors and serum oxidative stress levels (evaluated by the diacron-reactive oxygen metabolites [d-ROMs] test) or antioxidant capacity in the patients (evaluated by the biological antioxidant potential (BAP) test) was analyzed. A total of 238 patients were assessed for MTH1 protein levels using immunohistochemistry. Results: Among the 197 patients in the former cohort, 111 (56.3%) exhibited high MTH1 expression, while 86 (43.7%) exhibited low MTH1 expression. Male sex, smoking habit of ≥20 pack-years, squamous cell carcinoma, pathological stage ≥ II, tumor diameter ≥30 mm, lymph node metastases, pleural invasion, lymphatic permeation and vascular infiltration were significantly associated with high MTH1 expression ( p  < 0.05). The high MTH1 expression group had a significantly worse prognosis than that of the low MTH1 expression group (5-year overall survival: 81.6% vs. 92.3%, p  = 0.0011; 5-year disease-free survival: 55.0% vs. 83.7%, p  = 0.0002). d-ROMs and BAP test values were significantly higher in the high than in the low MTH1 expression group ( p  < 0.05). Conclusion: This study showed that MTH1 protein expression was closely related to factors associated with a high malignant potential and poor patient survival. MTH1 may be a novel therapeutic target for NSCLC.